A modified extragradient method for variational inclusion and fixed point problems in Banach spaces. Issue 10 (27th July 2021) - Sunthrayuth, Pongsakorn; Cholamjiak, Prasit
Abstract : In this work, we introduce a modified extragradient method for solving the fixed point problem of a nonexpansive mapping and the variational inclusion problem for two accretive operators in the framework of Banach spaces. We then prove its strong convergence under certain assumptions imposed on the parameters. As applications, we apply our main result to the variational inequality problem, split feasibility problem and the LASSO problem.